Language and Witchcraft as a Trade: Insights from, Machakos County, Kenya - Kiguru, Gatitu; Mwangi, Phyllis W.; Nthiga, Purity M.; Kimuyu, Caryn (Revista Internacional de Organizaciones, 2019)
Witchcraft is defined as the use of magical powers for healing, seeing into the future, causing harm or for religion. The belief in the powers of witchcraft is widespread in Africa. Due to these perceived magical powers people from different walks of life seek for various forms of treatments from witchdoctors. As such, witchcraft in Africa is a trade complete with a marked use of language that sustains in in modern society. This article reports on an analysis of language used by witchdoctors in Machakos County in Kenya, and respondents' views about witchcraft. The objectives of the study were twofold. One was to identify and describe the language strategies that mark witchcraft as trade. The second objective was to explore the socio-psychological factors governing the use of the language by witchdoctors. Two witchdoctors were purposively sampled: one male and one female. The primary data were collected through recorded interviews of the witchdoctors. It was found that the witchdoctors use various language strategies to attract and retain clientele and that these strategies are a factor of the socio-psychological environment in which the witchdoctors operate. Moreover, the study established that witchdoctor still find relevance in the modern Kenyan society because of prevalent beliefs about social and medical problems. This paper thus argues that language is an important tool in the witchcraft trade that serves to purposely obscure meaning in order to shroud the trade in secrecy, enhance social exclusion and consequently sustain the belief in the magical powers of the witchdoctors.